1985
DOI: 10.1161/01.str.16.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extra-intracranial arterial bypass on cerebral blood flow and oxygen metabolism in humans.

Abstract: SUMMARY Twelve patients, eleven with a carotid obstruction and one with an occlusion of the middle cerebral artery, were studied before and after a successful unilateral extra-intracranial arterial by-pass, (EIAB) using PET and the 15-0 steady-state technique to measure regional cerebral blood flow (CBF), oxygen extraction fraction and oxygen metabolic rate (CMRO 2 ). In the whole group of patients, both CBF and CMRO, increased significantly on both cerebral hemispheres after EIAB, returning toward control lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…12 This criticism was likely invalid given that multiple groups have reported that STA-MCA cortical branch anastomosis can reverse an abnormally elevated oxygen extraction fraction (OEF). 6,17,33,39 Second, many of the highest-risk patients may have been operated on outside of the trial and, therefore, not included in the study results, leading to a selection bias. 3,42 This claim was conclusively refuted by further data provided by the EC-IC Bypass Trial Investigators.…”
Section: International Ec-ic Bypass Trialmentioning
confidence: 99%
“…12 This criticism was likely invalid given that multiple groups have reported that STA-MCA cortical branch anastomosis can reverse an abnormally elevated oxygen extraction fraction (OEF). 6,17,33,39 Second, many of the highest-risk patients may have been operated on outside of the trial and, therefore, not included in the study results, leading to a selection bias. 3,42 This claim was conclusively refuted by further data provided by the EC-IC Bypass Trial Investigators.…”
Section: International Ec-ic Bypass Trialmentioning
confidence: 99%
“…In the contralateral hemisphere of the low CBF b subgroup, metabolic reduction was considered to be attributable to trans-hemispheric functional depression. Recovery of CMRO 2 in the contralateral hemisphere after bypass surgery supports this view [38] .…”
Section: Prognosis Of Patients With High Baseline Cbfmentioning
confidence: 69%
“…manipUlate the absolute value of OEF in relation to these pathophysiological circumstances (Baron et al, 1983;Wi se et al, 1983;Powers et al, 1984;Samson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%